Perancangan User Experience Aplikasi Promosi Wisata Lahor di Masa Pandemi menggunakan Metode Design Thinking - Nadia Putri Nur Ramadhani; Ratih Kartika Dewi; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
At the beginning of 2020, the Covid-19 pandemic had a detrimental impact on many parties. The tourism sector is one of the sectors that have been disadvantaged by the arrival of Covid-19. Since the presence of Covid-19, many tourist attractions have been closed due to government regulations to limit people from doing activities outside. This has resulted in considerable losses for the owners of tourist attractions due to the reduced number of visitors since the pandemic, one of which is the Lahor tourist spot. Visitors to Lahor's tourist attractions are increasingly deserted and have experienced a decline in turnover of more than 50%. With the hope of helping tourism managers in re-promoting Lahor tourist attractions, the author designed a user experience application for promoting Lahor tourist attractions during the pandemic using the design thinking method so that people can travel virtually at Lahor tourist attractions and visit them in person in the future. The author uses the design thinking method because based on existing research, design thinking is able to produce innovative solutions to problems. This study provides the final result in the form of a high-fidelity prototype. This test uses usability testing to test aspects of effectiveness, aspects of efficiency, and aspects of user satisfaction. From the results of the tests carried out, the design of this application solution got a score of 99% effectiveness aspect, 0.0868 goals/sec efficiency aspect, and 91% user satisfaction aspect. Based on the results of the System Usability Scale, the design solution for the Visit Lahor application is in the Grade A category, adjective rating excellent, and in the acceptable category.